Berbagai Dampak Hukuman (Punishment) dalam Pendidikan Terhadap Peserta Didik - Susmita Suharjo; Farid Pribadi (Universitas Lampung, 2021)
All humans are obliged to be educated. The objective of the subject of education is to improve the quality of oneself in order to become a complete person. In achieving that goal, education has tools to support its smooth running. One of the educational tools punishment which is punishment, has a profound impact on learners. The punishment in education is the punishment given to the learner aimed at edifying the offending learner. After the sentencing, the impact of the learner, the impact of each learner varied, to which in the study, researchers tried to dig up information on the impact of the punishment on the learner by using literature and secondary data, that is, data from previously existing sources such as journal articles, books, and scripts. Then the data was qualitatively analyzed using the miles and hubermans' methods. Analysis has resulted in some effect on learners. The effects are positive and dam impact.Keywords: Educational tools, punishment, and student DOI: http://dx.doi.org/10.23960/jiip.v3i2.23232